Long term cost-effectiveness analysis of IDegLira in the treatment of type 2 diabetes patients compared to GLP-1RA added to basal insulin after IDegLira entered the national reimbursement drug list in China - Dunming Xiao; Junling Weng; Lei Zhang; Chang Xing; Yan Wei; Yingyao Chen (PLoS ONE, 2025)
Background Degludec insulin liraglutide injection is the world’s first and only approved basal insulin GLP-1RA injection in China (GLP-1RA stands for Glucagon-Like Peptide-1 Receptor Agonist. This study aimed to evaluate the long-term cost-effectiveness of IDegLira versus GLP-1RA added to basal insulin regimen (combined regimen) for patients with type 2 diabetes in China. Methods Based on the perspective of the health system, the study adopts the Swedish Institute for Health Economics diabetes cohort model. The baseline and clinical efficacy data in the model are from the EXTRA study. The cost includes glucose-lowering medication, background treatment cost, and complication treatment costs. The prices of IDegLira and GLP-1RA are based on the national medical insurance payment standards. Insulin adopts the national volume-based procurement average price. Other cost and utility data are sourced from published literature. The health outcome indicator is quality-adjusted life years (QALYs). The simulation time horizon is 30 years. The discounting rate of cost and health outcomes is 5%. Results In clinical output, IDegLira could reduce the cumulative incidence of various chronic complications in patients compared to the combined regimen. The eye diseases (background, proliferative retinopathy, macular edema, and visual loss) decreased by 24.4%, 41.1%, 18.9%, and 12.2%, respectively. Neuropathy decreased by 17.3%. Proteinuria and end-stage renal disease decreased by 25.9% and 17.6% respectively. Ischemic heart disease, heart failure, and myocardial infarction (stroke) decreased by 0.8%, 1.1%, and 4.7%, respectively. In the base-case analysis, IDegLira compared to the combined regimen shows an incremental cost of -34,254 CNY and an incremental QALYs of 0.436. Under the threshold of 1 times the per capita GDP of China in 2022 (85,698 CNY), IDegLira is a dominant scheme with lower cost and better health outcome. In probabilistic sensitivity analysis, the probability of IDegLira being cost-effective is 100%, indicating that the base-case analysis results are robust. Conclusion Compared with the combined regimen, the use of IDegLira for Chinese patients with type 2 diabetes can improve long-term health output, save medical costs, and is a dominant scheme.